The Political Economy of Publicly Provided Private Goods - Sören Blomquist; Vidar Christiansen (Uppsala University, Department of Economics, 1998)
A large share of public funds is spent on private goods (education, health care, day care, etc.). This paper integrates two different approaches to the analysis of public provision of private goods. While normative public economics has established an efficiency case for such provision, the commonly held political economy view has been that it is an economically inefficient phenomenon generated by the political process. The present paper argues that the central mechanism studied in the normative approach is equally relevant to voting models of decisions on public provision. It is shown that under plausible information constraints economically efficient public provision of private goods will be part of politically rational decisions emerging from a median voter process or a representative democracy of political parties.
urn:nbn:se:uu:diva-2421
Keywords: D72; H21; H42; I38; 330; political economy; public provision; private goods; in-kind transfers